HIGH SCHOOL CULTURE MANAGEMENT: A CASE STUDY APPROACH - Salam, Khatibul Umam; Wijayanti, Wiwik; Khamid, Muh (JURNAL EDUSCIENCE, 2025)
Purpose – This research aims to determine the process of school culture management, inhibiting factors in developing school culture, and efforts to maintain school culture.Methodology—The research used a qualitative approach with a case study at SMA Negeri 1 Selong. The resource persons consisted of the principal, vice-principals, teachers, and students. Data collection used observation, interviews, and document studies. Data validity is in the form of credibility, dependability, transferability, and confirmability. Data analysis used an interactive model.Findings – The results of this study indicate that (1) School culture management includes: (a) Planning begins with a joint meeting under the leadership discussing long-term plans, then details into programs that support, then socialized. (b) Organizing the school culture in each activity, a coordinator is formed by vice-principals based on their respective competencies, then listed on the decree of assignment. (c) Actuating school culture includes the 5S Culture, discipline, orderly worship, kinship, clean culture, child-friendly, literacy, and Saturday culture. (d) Controlling is carried out directly by the PMO team by making notes and reports, which are then evaluated. (2) The inhibiting factor is that most school members still do not understand the true meaning of school culture. How to overcome this is by increasing collaboration, commitment, and taking a persuasive personal approach (3) Efforts to maintain school culture prioritize consistency such as socialization, planting P5, activating coaching, and evaluating activities in the previous year to be developed.Significance—This study's results will greatly benefit students, the government, and education observers.Purpose – This research aims to determine the process of school culture management, inhibiting factors in developing school culture, and efforts to maintain school culture.Methodology—The research used a qualitative approach with a case study at SMA Negeri 1 Selong. The resource persons consisted of the principal, vice-principals, teachers, and students. Data collection used observation, interviews, and document studies. Data validity is in the form of credibility, dependability, transferability, and confirmability. Data analysis used an interactive model.Findings – The results of this study indicate that (1) School culture management includes: (a) Planning begins with a joint meeting under the leadership discussing long-term plans, then details into programs that support, then socialized. (b) Organizing the school culture in each activity, a coordinator is formed by vice-principals based on their respective competencies, then listed on the decree of assignment. (c) Actuating school culture includes the 5S Culture, discipline, orderly worship, kinship, clean culture, child-friendly, literacy, and Saturday culture. (d) Controlling is carried out directly by the PMO team by making notes and reports, which are then evaluated. (2) The inhibiting factor is that most school members still do not understand the true meaning of school culture. How to overcome this is by increasing collaboration, commitment, and taking a persuasive personal approach (3) Efforts to maintain school culture prioritize consistency such as socialization, planting P5, activating coaching, and evaluating activities in the previous year to be developed.Significance—This study's results will greatly benefit students, the government, and education observers.Keywords: Management School, Culture Management